New concepts of theory of gearing and a method for reverse synthesis of the gearing - Phuc, Nguyen Thien (Vietnam Journal of Mechanics, 2011)
In this paper,  the concepts of theory of gearing are developed by the synthesis of the results of our researches for years into theorical development and practical application of the generation of gear. A method of the reverse synthesis of the gearing is introduced in the third part.